PENGARUH MODEl DIRECT INTRUCTION (DI) BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MEMPRODUKSI TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 5 PARIAMAN - Zuraida Khairani; Dwi Mutia Chan; Najmi Hayati (STKIP Pesisir Selatan, 2023)
The purpose of this study is three things. First, to describe the skills of producing text descriptions for Class VII students of SMP Negeri 5 Pariaman before applying the Problem-Based Learning (PBL) Direct Direct Model. Second, describe the skills of producing description texts for VII grade students of SMP Negeri 5 Pariaman after applying the Problem Based Learning (PBL) based Direct Intruction Model (DI). Third, analyze the influence of the Direct Intruction Model (DI) based on Problem Based Learning (PBL) on the skills of producing text descriptions for grade VII students of SMP Negeri 5 Pariaman. The research sample was students of class VII.4, amounting to 30 people. Based on the results of data analysis and discussion the following conclusions are obtained. First, the ability to produce text descriptions for grade VII.4 students of SMP Negeri 5 Pariaman before applying the Problem Based Learning (PBL) based Direct Intruction Model (PBL) with an average value of 69.03. Second, the ability to produce text descriptions for grade VII 4 students of SMP Negeri 5 Pariaman after applying the Problem Based Learning (PBL) based Direct Instruction Model with an average grade of 78.03. Third, the application of the Model Direct Intruction (DI) based on Problem Based Learning (PBL) after t-test at the level of 0.95, obtained tcount> ttable or 4.43> 1.70. So H0 is rejected and H1 is accepted. This means that the application of Problem Based Learning (PBL) based Direct Intruction Model (DI) is feasible to be applied to the skills of producing description texts for grade VII.4 students of SMP Negeri 5 Pariaman.